Analysis of Waste Encumbrances on Building Procurement in Southwest States of Nigeria - Tongo, Samuel Osayamen; Uzzi, Festus O. (NIU Journal of Humanities; Vol 6 No 2 (2021): KIU Journal of Humanities, Vol. 6 No. 2, June 2021, 2021)
The study examines waste encumbrances on procurement of building projects in the southwest state of Nigeria. The study haphazardly sampled 261 practising professionals comprising of engineer, quantity surveyor, builder, architect, project manager, and planner in the study area. The data was collected through the use of a questionnaire. However, the result of the findings was analysed using the statistical package for social science (SPSS) application, and these were presented in tables. The results of the study found that; undefined in the scope of the project, waste management not design, choice of consultant, lack of early collaborative engagement, unclear brief/project definition, and timing rated 53.80%, 46.10%, 38.40% and 30.70% respectively were amidst the leading encumbrance on building procurement in the study area. The study also revealed that change in design, design and construction detail error, ambiguity and inconsistency in drawing, design error, variation/change order request, and last-minute were retest highest as among factors, and wrong choice of contractors’, tender/contract document incomplete at the commencement of construction, and absence/poorly defined waste management responsibilities. Based on this, the selection process for buildings contractor, and workers should be selected based on experiences, measures that will ensure clarify of design, brief and construction bill should be in place. This will eliminate the present burden of material waste, price increase, project delay in term of time witness across different building projects in southwest Nigeria. Keywords: Analysis, Encumbrance, Waste, Building Procurement, Southwest